An Update Overview on Brain Imaging Studies of Internet Gaming Disorder - Weinstein, Aviv M. (Frontiers in Psychiatry, 2017)
There is a growing number of studies on structural and functional brain mechanisms underlying Internet Gaming Disorder (IGD). Recent Functional Magnetic Resonance Imaging (fMRI) studies showed that IGD adolescents and adults had reduced gray matter volume in regions associated with attention motor coordination executive function and perception. Adolescents with IGD showed lower white matter integrity measures in several brain regions that are involved in decision-making, behavioral inhibition and emotional regulation. IGD adolescents had also disruption in the functional connectivity in areas responsible for learning memory and executive function, processing of auditory, visual, and somato-sensory stimuli and relay of sensory and motor signals. IGD adolescents also had decreased functional connectivity of PFC-striatal circuits, increased risk-taking choices and impaired ability to control their impulses similar to other impulse control disorders. Recent studies indicated that altered executive control mechanisms in ADHD would be a predisposition for developing IGD. Finally, Patients with IGD have also shown an increased functional connectivity of several executive control brain regions that may related to comorbidity with ADHD and depression. The behavioral addiction model argues that IGD shows the features of excessive use despite adverse consequences, withdrawal phenomena, and tolerance that characterize substance use disorders. The evidence supports the behavioral addiction model of IGD by showing structural and functional changes in the mechanisms of reward and craving (but not withdrawal) in IGD. Future studies need to investigate white matter density and functional connectivity in IGD in order to validate these findings. Furthermore, more research is required about the similarity in neuro-chemical and neuro-cognitive brain circuits in IGD and co-morbid conditions such as ADHD and depression.